BODIPY‐Based Fluorescent Thermometer as a Lysosome‐Targetable Probe: How the Oligo(ethylene glycols) Compete Photoinduced Electron Transfer. Issue 8 (29th December 2014) - Wang, Hua; Wu, Yongquan; Shi, Yanlin; Tao, Pan; Fan, Xing; Su, Xinyan; Kuang, Gui‐Chao
Abstract: A novel BODIPY‐based fluorescent thermometer, which shows a lysosome‐targeting property, was successfully prepared. Due to the electron‐donating ability of the oligo(ethylene glycols), the photoinduced electron‐transfer pathway from morpholine to BODIPY dye is blocked. The fluorescence of the thermometer quenched by intramolecular rotation at room temperature was progressively enhanced during heating due to the increased microviscosity around the fluorophore. Abstract : It′s a heat wave : A BODIPY (boron‐dipyrromethene)‐based fluorescent thermometer, which shows a lysosome‐targeting property, was successfully prepared. The fluorescence of the thermometer, quenched by intramolecular rotation at room temperature, was progressively enhanced during heating (see figure) due to the increased microviscosity around the fluorophore.